Effect of radical prostatectomy surgeon volume on complication rates from a large population-based cohort - Almatar, Ashraf; Wallis, Christopher J.D.; Herschorn, Sender; Saskin, Refik; Kulkarni, Girish S.; Kodama, Ronald T.; Nam, Robert K. (Canadian Urological Association Journal, 2016)
Introduction: Surgical volume can affect several outcomes following radical prostatectomy (RP). We examined if surgical volume was associated with novel categories of treatment-related complications following RP. Methods: We examined a population-based cohort of men treated with RP in Ontario, Canada between 2002 and 2009. We used Cox proportional hazard modeling to examine the effect of physician, hospital and patient demographic factors on rates of treatmentrelated hospital admissions, urologic procedures, and open surgeries. Results: Over the study interval, 15 870 men were treated with RP. A total of 196 surgeons performed a median of 15 cases per year (range: 1–131). Patients treated by surgeons in the highest quartile of annual case volume (>39/year) had a lower risk of hospital admission (hazard ratio [HR]=0.54, 95% CI 0.47–0.61) and urologic procedures (HR=0.69, 95% CI 0.64–0.75), but not open surgeries (HR=0.83, 95% CI 0.47‒1.45) than patients treated by surgeons in the lowest quartile (<15/year). Treatment at an academic hospital was associated with a decreased risk of hospitalization (HR=0.75, 95% CI 0.67–0.83), but not of urologic procedures (HR=0.94, 95% CI 0.88–1.01) or open surgeries (HR=0.87, 95% CI 0.54–1.39). There was no significant trend in any of the outcomes by population density. Conclusions: The annual case volume of the treating surgeon significantly affects a patient’s risk of requiring hospitalization or urologic procedures (excluding open surgeries) to manage treatment-related complications.